Perubahan Histopatologi Ovarium, Uterus, dan Ginjal Marmut (Cavia cobaya) yang Diberi Ekstrak Daun Binahong (Anredera cordifolia) - Wijayanti, Dwi; Setiatin, Enny Tantini; Kurnianto, Edy (Jurnal Veteriner; Vol 20 No 2 (2019), 2019)
Binahong (Anredera cordifolia) leaf extract has a benifficial function as an antimicrobial, heals topical wounds and accelerates the appearance of postpartum estrus. The purpose of this study was to analyze the histophatology and toxicity of ovarian, uterine, and kidney of guinea pig (Cavia cobaya) given A. cordifolia leaf extract. A total of eight females of C. cobaya were used in study, weighing ± 425 g. Treatments were given 0, 10, 50 and 90 mg of A. cordifolia leaf extract/ head, designated as T0, T1, T2 and T3, respectively. Two females were subjected for each treatment. Leaf extract of A. cordifolia was administered orally for 10 days prepartum. Observation consisted of ovarian histopathology, uterus (amount of inflammation and edema) and toxicity of kidney organs. The data obtained was analyzed by using univariate method and descriptively. The results showed there were no damage found on ovarian histology. The fastest follicular growth was found on guinea pigs treated with the dose of 50 mg of A. cardifolia/head. The inflammatory cells found in the uterus treated with 50 mg/head of A. cordifolia leaf extract were four types of inflammatory cells, at least compared to the doses of 0, 10 and 90 mg/head. Total edema in the myometrium and endometrium showed a score of 1 and 0, respectively. The dose of A. cordifolia leaf extract of 10 to 50 mg/head secured for kidney compared to a dose of 0 and 90 mg/head with glomerulonephritis and nephritis. The best treatment to accelerate follicular development, reduce inflammation and not toxic was the treatment of A. cordifolia leaf extract of 50 mg/head orally.